Interplay between improved interaction rates and modified cosmological histories for dark matter - Biondini, Simone (Frontiers in Physics, 2023)
A novel particle has been and still is an intriguing option to explain the strong evidence for dark matter in our universe. To quantitatively predict the dark matter energy density, two main ingredients are needed: interaction rates and an expansion history of the universe. In this work, we explore the interplay between recent progress in the determination of particle production rates and modified cosmological histories. For the freeze-out mechanism, we focus on Sommerfeld and bound-state effects, which boost and make dark matter pair annihilation more efficient. As regards the freeze-in option, we include thermal masses, which enter the decay processes that produce dark matter, and we find that they can suppress or enhance the dark matter yield. We consider a class of modified cosmological histories that induce a faster universe expansion, and we assess their effect in combination with improved particle interaction rates on the dark matter energy density